Genetic Mapping of Genes Concerned with Glutamyl Polypeptide Production by Bacillus licheniformis and a Study of Their Relationship to the Development of Competence for Transformation - McCuen, R. W. (1971)
By transduction with SP-15, we have mapped some of the genetic sites involved in glutamyl polypeptide (Pep) production by Bacillus licheniformis 9945A. Eleven peptide mutations were assigned to group 1 which lies between the gly-42 and his-6 markers. Three other mutations were assigned to group 2 which lies between the ade-2 and str-1 sites. A series of 28 additional Pep(−) mutants did not belong to either group 1 or 2; the chromosomal location of those peptide mutations is unknown. All three mutants of group 2 were highly transformable, but only two of group 1 transformed well under the conditions employed. Knowing the chromosomal markers that were linked to peptide mutations made it possible to investigate the effect peptide mutations might have on the development of competence for transformation. Nontransformable organisms were rendered transformable upon the introduction, by transduction, of Pep(−) mutations from transformable strains. These results supported the conclusion that the ability of cells to develop competence for transformation when grown under appropriate conditions was related to the physiological effects of particular peptide mutations.